Contribution to the study of female genital moniliasis - Benavente Lozada, Benjamin (2015)
This work is based on the study of vaginal discharge smears and culture thereof, made to the HMC from March 1958 to March 1959. Terminología.-Many denominations have been created to name this infestation fungal genital system. Currently they are known in the literature over 80 names for fungal vaginal fluids. We continue using the vaginal Moniliasis because it is a term that has been imposed in medical language. We must make the proviso that the term Moniliasis, in the medical sense, does not mean it has the same meaning in the botanical order.